Carbon fiber-based carbon-silicon composite material, preparation method thereof, negative plate and battery
Through the carbon-silicon composite material with a multi-dimensional carbon fiber core-shell structure, the gap and carbon fiber-covered silicon nanoparticles are constructed using PDDA, which solves the problem of interface rupture caused by silicon particle expansion and improves the cycle stability and electrochemical performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411192633.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-27
AI Technical Summary
Silicon particles rupture in lithium-ion batteries due to volume expansion, limiting their application, and existing silicon-carbon composites perform poorly in cycling performance and first-time Coulomb efficiency.
A carbon-silicon composite material with a multi-dimensional carbon fiber core-shell structure is used to construct gaps through a multi-layered cladding structure of silicon nanoparticles and carbon fibers, using PDDA as a sacrificial template to create a gap, providing buffer space and improving conductivity.
Excellent rate performance, cycle stability and low expansion effects are achieved, improving the overall mechanical strength and electrochemical properties of the material.
Smart Images

Figure CN119208552A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon-carbon materials, and in particular to the technical field of negative electrode materials, and in particular to a carbon fiber-based carbon-silicon composite material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] Silicon particles will undergo significant volume expansion during the lithium insertion process, resulting in the rupture of the solid-electrolyte interface (SEI film) formed on the surface of the material. The exposed surface will produce a new SEI film during the subsequent lithium insertion process, which limits the practical application of silicon in lithium-ion batteries.
[0003] Carbon-silicon composite materials are currently one of the effective ways to meet the internal space requirements caused by silicon expansion without causing repeated damage to the SEI film. Carbon-silicon composite materials, on the one hand, can artificially introduce a certain amount of space inside the particles in terms of physical structure through silicon-carbon composite technology to meet the needs of silicon expansion; on the other hand, they can prevent solvated lithium from entering the material particles, preventing the formation of SEI films inside the material particles and gradually occupying their internal space.
[0004] The current silicon-carbon composite materials use pure silicon powder as the silicon source. Due to the low conductivity of silicon powder and the large volume expansion rate during the cycle, it is easy to cause structural collapse and the shedding of active materials in the electrode, resulting in poor cycle performance of the material. Alternatively, silicon dioxide can be used. The bond length of the Si-O-Si chemical bond is about twice that of Si-Si. Its existence expands the internal space of the material from the atomic structure, greatly alleviating the expansion problem caused by the embedding of metallic lithium. However, due to the presence of silicon dioxide and the formation of lithium oxide and lithium silicate during the lithium charging process, the initial coulomb efficiency is low and the cycle life is not ideal. Summary of the invention
[0005] The present invention provides a carbon fiber-based carbon silicon composite material which can be used as a negative electrode material of a battery and has excellent rate performance, cycle performance and low expansion effect.
[0006] The present invention provides a carbon fiber-based carbon silicon composite material. The carbon silicon composite material is a multidimensional carbon fiber core-shell structure, including a first core-shell structure and a second core-shell structure. The first core-shell structure is a core-gap-shell structure with silicon nanoparticles as the core and a carbon coating layer of a first carbon source as the shell; the second core-shell structure has the first core-shell structure as the core and is distributed in a carbon fiber structure formed by a second carbon source.
[0007] Furthermore, the donor of the first carbon source is a resin or polydopamine. Specifically, the resin is a phenolic resin or a derivative thereof.
[0008] Furthermore, the donor of the second carbon source is a spinnable polymer. Specifically, the spinnable polymer is one or more of polyacrylonitrile (PAN), polyethylene oxide, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polystyrene and polyamide.
[0009] Furthermore, the gap is constructed by using polydiallyldimethylammonium chloride as a sacrificial template.
[0010] Furthermore, the thickness of the carbon coating layer of the first core-shell structure is 30-50 nm.
[0011] Furthermore, the particle size of the silicon nanoparticles is 5-15 nm.
[0012] Furthermore, the particle size of the first core-shell structure is 100-300 nm.
[0013] Furthermore, the particle size of the first core-shell structure is 100-300 nm.
[0014] Furthermore, the length of the carbon fiber is 10-80 μm.
[0015] Furthermore, the carbon fiber is hollow carbon fiber.
[0016] Further, the silicon content of the carbon fiber-based silicon-carbon composite material is 30-45%. Further, the ID / IG value of the carbon fiber-based silicon-carbon composite material is 0.70-0.90.
[0017] In another aspect, the present invention provides a method for preparing a carbon-silicon composite material with a multi-dimensional carbon fiber core-shell structure, comprising the following steps:
[0018] S1: mixing silicon powder and surfactant in a solvent to obtain an intermediate product A;
[0019] S2: taking the intermediate product A and mixing it with a polymerizable monomer in a solution, and obtaining a first carbon source coated product B by in-situ polymerization;
[0020] S3: adding the first carbon source coated product B to a spinnable polymer solution to prepare a spinning mixture and performing electrospinning to obtain spinning fibers;
[0021] S4: The spun fibers in step S3 are carbonized to obtain the carbon fiber-based silicon-carbon composite material.
[0022] Further, in step S1, the surfactant is polydiallyldimethylammonium chloride; and / or the solvent is deionized water; and / or the mass volume ratio of silicon powder to surfactant is 20-50g:1L; and / or the volume ratio of surfactant to solvent is 1-5:10-20.
[0023] Furthermore, in step S2, the polymerization monomers include at least one phenolic compound and at least one aldehyde compound, at least one phenolic compound and a combination of trioxane or glucose, or dopamine hydrochloride. The donor of the first carbon source is a phenolic resin or a derivative thereof, or polydopamine.
[0024] Among them, the phenolic compounds include polyphenolic compounds, and may further contain at least one of resorcinol, alkylresorcinol, catechol, hydroquinone, pyrogallol or tannic acid; the aldehyde compounds include at least one of formaldehyde, rose formaldehyde, acetaldehyde, propionaldehyde, furfural, benzaldehyde, butyraldehyde.
[0025] Furthermore, the mass ratio of the polymerized monomer to the silicon powder is 1-10:1.
[0026] Furthermore, the solution is an alkaline solution, preferably an ammonia solution or a buffer solution.
[0027] Furthermore, the thickness of the coating layer of the first carbon source coated product B is 30-50 nm.
[0028] Furthermore, the particle size of the first carbon source coated product B is 120-250 nm.
[0029] Further, in step S3, the spinnable polymer of the second carbon source is one or more of polyacrylonitrile, polyethylene oxide, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polystyrene and polyamide. The concentration of the spinnable polymer solution of the second carbon source is 30-350 g / L.
[0030] The solvent of the spinnable polymer solution includes at least one of N,N-dimethylformamide DMF, dimethylacetamide DMAc, methanol or acetone; the mass ratio of the spinnable polymer to the silicon powder is 5-20:1.
[0031] Furthermore, the electrospinning process parameters include: voltage 140-160 kV, feed rate 0.5-2 mL / h, and collection distance 12-20 cm.
[0032] Furthermore, in step S4, the carbonization temperature is 700-1000°C; and / or the carbonization time is 0.5-30h; and the heating rate is 2-10°C / min.
[0033] In yet another aspect, the present invention provides a negative electrode sheet comprising any of the aforementioned materials or a material prepared by any of the aforementioned preparation methods.
[0034] In another aspect, the present invention provides a battery, comprising the aforementioned negative electrode sheet or a negative electrode made of any of the aforementioned materials or materials prepared by any of the aforementioned preparation methods.
[0035] Furthermore, the battery is a button cell; and / or the first discharge specific capacity is greater than 1360 mAh·g -1 ; and / or, specific capacity > 1070 mAh g after 200 cycles -1 ; and / or, first efficiency>87%.
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] 1. The present invention constructs a carbon-silicon composite negative electrode material with a multi-dimensional carbon fiber core-shell structure, including a first core-shell structure and a second core-shell structure. The first core-shell structure is a core-gap-shell structure, using silicon powder as a silicon source, silicon nanoparticles as a core, and a carbon layer to form a separate core-shell structure particle containing a gap; the second core-shell structure is distributed in the carbon fiber with the first core-shell structure as a core. The multilayer structure and carbon fiber can effectively disperse the mechanical stress caused by the deformation of silicon particles; the silicon nanoparticles are evenly coated inside the carbon nanofibers, which improves the conductivity, rate performance and cycle stability of the composite material.
[0038] 2. The carbon-silicon composite negative electrode material with a multi-dimensional carbon fiber core-shell structure of the present invention uses PDDA as a sacrificial template to construct a gap, providing a buffer space for the volume expansion of silicon particles. Using PDDA as a sacrificial template, the gap is constructed by thermal decomposition and sacrifice, providing a buffer space for the volume expansion of silicon particles. Silicon nanoparticles can be completely embedded in the interior of the RF resin carbon, and a unique core-shell structure is constructed, which buffers the volume effect and improves the cyclic stability of the material.
[0039] 3. The multi-dimensional carbon fiber core-shell structure constructed by the present invention uniformly wraps silicon nanoparticles of controllable size inside the carbon layer constructed by RF resin, and uses electrostatic spinning to tightly wrap the core-shell structure silicon carbon in the carbon nanofiber, so that the material obtains an excellent conductive carbon network. The special multi-layer coating structure gives the material better mechanical strength, prevents the internal silicon particles from expanding and causing structural rupture; it can better buffer the expansion stress of the material and improve the cyclic stability of the material; at the same time, the conductive network helps to improve the electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0041] Figure 1 The SEM image (1 um) of the carbon fiber-based silicon-carbon composite material described in the embodiment of the present invention is shown.
[0042] Figure 2 The TEM image (0.5 um) of the carbon fiber-based silicon-carbon composite material described in the embodiment of the present invention is shown.
[0043] Figure 3 The figure is a schematic diagram of a process for preparing a carbon fiber-based carbon silicon composite material according to an embodiment of the present invention.
[0044] Figure 4 The preparation process of the carbon fiber-based carbon silicon composite material described in the embodiment of the present invention is shown.
[0045] Figure 5 The figure shows the rate performance of the carbon fiber-based carbon silicon composite material according to the embodiment of the present invention. DETAILED DESCRIPTION
[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] One embodiment of the present invention provides a carbon fiber-based carbon silicon composite material, wherein the carbon silicon composite material is a multi-dimensional carbon fiber core-shell structure (such as Figure 1 , 2 As shown), it includes a first core-shell structure and a second core-shell structure. The first core-shell structure is a core-gap-shell structure with silicon nanoparticles as the core and a carbon coating layer of the first carbon source as the shell; the second core-shell structure has the first core-shell structure as the core and is distributed in the carbon fibers formed by the second carbon source.
[0048] The carbon-silicon composite material of the multi-dimensional carbon fiber core-shell structure of the embodiment of the present invention includes a first core-shell structure and a second core-shell structure. The first core-shell structure is a core-gap-shell structure with silicon nanoparticles as the core to provide a buffer space for the volume expansion of silicon particles; the second core-shell structure is distributed in the carbon fiber with the first core-shell structure as the core. The multi-layer coating structure and the carbon fiber can effectively disperse the mechanical stress caused by the deformation of the silicon particles; the silicon nanoparticles are uniformly coated inside the carbon nanofibers, which improves the conductivity, rate performance and cycle stability of the composite material.
[0049] The embodiment of the present invention constructs a unique core-shell structure, wrapping the 3D silicon-carbon core-shell structure in a 1D carbon nanofiber skeleton, which can not only utilize the carbon nanofiber as a supporting skeleton to enhance the overall mechanical strength of the material, but also further improve the electrochemical properties of the material through the synergistic effect between the carbon nanofiber and the carbon shell, such as improving the cycle stability and rate performance.
[0050] In another embodiment, the donor of the first carbon source may be a resin or polydopamine.
[0051] Suitable resins may be phenolic resins or their derivatives.
[0052] The donor of the second carbon source is a spinnable polymer. A spinnable polymer refers to a polymer that can be converted into a spinning fiber by a spinning process such as electrospinning, solution spinning, melt spinning, etc. Applicable spinnable polymers can be one or more of polyacrylonitrile (PAN), polyethylene oxide, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polystyrene and polyamide.
[0053] Polyacrylonitrile PAN is spun to form 1D carbon fiber. The carbon coating layer of the first carbon source is a shell and the 3D core-shell structure formed by silicon nanoparticles as the core is distributed in the aforementioned fiber structure. In this way, the silicon nanoparticles are evenly wrapped inside the carbon layer of the core-shell structure, and the core-shell structure is tightly wrapped in the carbon nanofibers, so that the material obtains an excellent conductive carbon network. It not only gives the material better mechanical strength and prevents the internal silicon particles from expanding and causing structural rupture; it can also improve the material's cycle stability and electrochemical performance.
[0054] In another embodiment, the carbon-silicon composite material uses polydiallyldimethylammonium chloride (PDDA) as a sacrificial template to construct a gap, and constructs the gap between the silicon nanoparticle core and the carbon shell. In the composite material of this embodiment, the core-shell structure particles formed by RF resin coating single silicon particles (there is a gap between RF and silicon particles, formed by thermal decomposition of PDDA) are redistributed inside the PAN fiber. Different from using solvent to dissolve the carbon shell to construct a gap, the present invention constructs the gap by thermal decomposition of PDDA. In this structure, single silicon nanoparticles are coated in the PDDA carbon coating layer, instead of multiple silicon nanoparticles sticking together, and then coated under the RF resin carbon shell to form a 3D core-shell structure particle, which is then evenly distributed in the PAN fiber structure, and the fiber structure crosses / intersperses to form a tight and stable network structure, which is beneficial to the improvement of electrochemical performance.
[0055] In another embodiment, the particle size of the silicon nanoparticles is 5-15 nm, for example, 5-8 nm, 5-10 nm, 8-15 nm, 6 nm, 7 nm, 8 nm, 10 nm, 12 nm, 13 nm, 14 nm, 15 nm, etc.
[0056] The particle size of the first core-shell structure is 100-300 nm, for example, 100-150 nm, 100-200 nm, 200-300 nm, 150-200 nm, 150-300 nm, etc., for example, 100 nm, 110 nm, 120 nm, 150 nm, 200 nm, 300 nm, etc.
[0057] The thickness of the carbon coating layer of the first carbon source is 30-50 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc.
[0058] In the embodiment of the present invention, the length of the carbon fiber may be 10-80 μm.
[0059] In the embodiment of the present invention, the carbon fiber may be a hollow carbon fiber, for example, a hollow strip, such as a carbon fiber tube, with a cavity structure inside the fiber. In the carbon-silicon composite negative electrode material of the embodiment of the present invention, the silicon nanoparticles are evenly distributed in the carbon fiber tube in a 3D core-shell structure, and a large number of hollow pores are distributed inside the carbon fiber, providing a buffer space for the volume deformation of the silicon particles, thereby improving the cycle characteristics of the material.
[0060] like Figure 3 As shown, another embodiment of the present invention provides a method for preparing a carbon fiber-based carbon-silicon composite material, comprising the following steps:
[0061] S1: mixing silicon powder and surfactant in a solvent to obtain an intermediate product A;
[0062] S2: taking the intermediate product A and mixing it with a polymerizable monomer in a solution, and obtaining a first carbon source coated product B by in-situ polymerization;
[0063] S3: adding the first carbon source coated product B to a spinnable polymer solution to prepare a spinning mixture and performing electrospinning to obtain spinning fibers;
[0064] S4: The spun fibers in step S3 are carbonized to obtain the carbon fiber-based silicon-carbon composite material.
[0065] The carbon fiber-based silicon-carbon composite material prepared in the embodiment of the present invention is a multi-dimensional carbon fiber core-shell structure. The silicon content of the silicon-carbon composite material is 30-45%.
[0066] The ID / IG value of the silicon-carbon composite material is 0.70-0.90.
[0067] ID / IG value refers to the ratio of drain current to gate current. A higher ID / IG value indicates that there are more defects on the surface of the material, which can serve as active sites for electrochemical reactions, thereby potentially improving the electrochemical properties of the material, such as specific capacitance and rate performance.
[0068] In step S1, the surfactant may be polydiallyldimethylammonium chloride (PDDA). The solvent may be deionized water. The intermediate product A is a carbon-silicon coated structure of nanoparticles coated with PDDA as a carbon source.
[0069] The amount of surfactant added is such that the mass volume ratio of silicon powder to surfactant is 20-50 g:1 L. For example, it can be 20 g:1 L, 25 g:1 L, 30 g:1 L, 35 g:1 L, 40 g:1 L, 20-40 g:1 L, and so on.
[0070] The volume ratio of surfactant to solvent is 1-5:10-20. For example, it can be 1:10, 1:20, 1:15, 2:15, 3:30, 5:20, 3:10, 4:10, 4:15, 5:10, 5:15, 5:20, 1-5:20, 1-5:15-20, 2-5:10-20, etc.
[0071] The particle size of the silicon powder may be 5-15 nm, for example, 5-8 nm, 5-10 nm, 5-12 nm, etc.
[0072] The particle size of the intermediate product A may be 20-150 nm, for example, 20-35 nm, 20-45 nm, 20-50 nm, 20-100 nm, 30-50 nm, 30-80 nm, 30-150 nm, 40-100 nm, 40-120 nm, 50-100 nm, and the like.
[0073] Specifically, step S1 may be: mixing silicon powder and polydiallyldimethylammonium chloride (PDDA) solution in water, stirring, centrifuging, and washing to obtain a carbon-silicon coated structure in which silicon nanoparticles are coated with PDDA as a carbon source.
[0074] In step S2, the intermediate product A obtained in step S1 is coated with a carbon coating layer formed by the first carbon source by in-situ polymerization. The donor of the first carbon source may be a phenolic resin or a derivative thereof, or polydopamine.
[0075] Specifically, the intermediate product A is mixed with a polymerizable monomer of a resin or polydopamine in a solution, and the first carbon source coated product B is obtained by in-situ polymerization.
[0076] The particle size of the first carbon source coated product B is 120-250 nm, for example, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, etc.
[0077] The thickness of the carbon coating layer of the first carbon source coated product B is 30-50 nm, for example, 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm, 50 nm, etc.
[0078] In the present invention, the polymerizable monomer, also called the polymerizable precursor, refers to a monomer that can generate a phenolic resin or its derivatives, or polydopamine through a condensation or polymerization reaction. The amount of the polymerizable monomer is such that the mass ratio of the polymerizable monomer to the silicon powder is 1-10:1 based on the mass of the silicon powder.
[0079] The polymerizable monomer of the resin may be a combination of a first polymerizable monomer and a second polymerizable monomer, wherein the first polymerizable monomer is at least one phenolic compound; and the second polymerizable monomer is at least one aldehyde compound, trioxane or glucose. The polymerizable precursor of polydopamine may be dopamine hydrochloride.
[0080] The phenolic compound includes a polyphenol compound, and may further include at least one of resorcinol, alkylresorcinol, catechol, hydroquinone, pyrogallol or tannic acid.
[0081] The aldehyde compound includes at least one of formaldehyde, rose formaldehyde, acetaldehyde, propionaldehyde, furfural, benzaldehyde and butyraldehyde.
[0082] For example, the donor of the first carbon source may be a phenolic resin. The polymerized monomer of the resin may be a combination of a first polymerized monomer and a second polymerized monomer. The first polymerized monomer is at least one phenolic compound; the second polymerized monomer is at least one aldehyde compound, trioxane or glucose. The molar ratio of the first polymerized monomer (phenol) to the second polymerized monomer (aldehyde) may be 5-9:1. For example, it may be 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, etc.
[0083] Step S2 may be to take the intermediate product A and the phenolic compound, add them to an ammonia solution and mix them, and then add the aldehyde compound and mix them. Specifically, add ammonia solution, the phenolic compound and deionized water to the intermediate product A, sonicate and stir, then dropwise add the aldehyde compound solution, stir and centrifuge.
[0084] The aldehyde compound may be a solution with a mass fraction of 35-37%, such as a formaldehyde solution. At this time, the mass volume ratio of the phenolic compound to the aldehyde compound solution may be 100-220 g: 0.01-0.03 L.
[0085] The mass fraction of ammonia water is 20-30%, and the volume mass ratio of ammonia water to phenolic compounds is 1 mL: 5-20 g.
[0086] For another example, the donor of the first carbon source may be polydopamine, and the polymerization monomer may be dopamine hydrochloride. Step S2 may be, adding deionized water to the intermediate product A, ultrasonicating, adding a buffer solution, and adding dopamine hydrochloride after dissolving. Specifically, trihydroxyaminomethane may be used as a buffer solution to adjust the alkaline environment. Step S2 may be, adding deionized water to the intermediate product A, ultrasonicating, adding trihydroxyaminomethane (tris), adding dopamine hydrochloride (PDA) after dissolving, and stirring and centrifuging thoroughly. The mass ratio of dopamine hydrochloride to silicon powder is 1-10:1. The mass ratio of trihydroxyaminomethane to dopamine hydrochloride is 3-10:1.
[0087] The power of ultrasound is , the frequency of ultrasound machine is 35-45kHz, and the time of ultrasound is 5-15min.
[0088] In step S3, the first carbon source coated product B obtained in step S2 is added to a spinnable polymer solution to prepare a spinning mixture and electrospinning is performed to obtain spinning fibers formed by the second carbon source.
[0089] The spinnable polymer may be one or more of polyacrylonitrile, polyethylene oxide, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polystyrene and polyamide.
[0090] The concentration of the spinnable polymer solution may be 30-350 g / L, for example, 30, 50, 100, 150, 200, 300, 350 g / L, etc.
[0091] The solvent of the spinnable polymer solution may be at least one of N,N-dimethylformamide (DMF), dimethylacetamide DMAc, methanol or acetone.
[0092] The amount of the spinnable polymer used is such that, based on the mass of the silicon powder, the mass ratio of the spinnable polymer to the silicon powder is 5-20:1, for example, 5:1, 8:1, 10:1, 12:1, 15:1, 18:1, 20:1, etc.
[0093] The electrospinning process parameters include: voltage 140-160 kV, feed rate 0.5-2 mL / h, and collection distance 12-20 cm.
[0094] In one embodiment, step S3 may specifically be: dissolving polyacrylonitrile PAN in N,N-dimethylformamide (DMF) to obtain a polyacrylonitrile solution, adding the product Si@PDDA@RF obtained in step S2 to the polyacrylonitrile solution, mixing to obtain a spinning mixture, and adding the mixture to an electrospinning device to obtain spinning fibers.
[0095] In the embodiment of the present invention, a 3D core-shell structure with RF resin as a carbon shell and silicon nanoparticles as a core is distributed in a 1D carbon nanofiber through electrospinning. The multi-layer coating structure constructed by the carbon nanofiber and the RF resin carbon shell provides a buffer for the volume deformation of the silicon particles and prevents the internal silicon particles from expanding and causing structural rupture. At the same time, the carbon fibers are interconnected to form a network structure with the 3D core-shell structure of silicon particles filled inside, which is beneficial to electron transmission and material diffusion, and improves the cyclic stability of the material.
[0096] In step S4, the spun fibers in step S3 are carbonized to obtain the carbon fiber-based silicon-carbon composite material.
[0097] The carbonization temperature may be 700-1000° C. For example, it may be 700-900° C., 800-1000° C., 800-900° C., etc. For example, it may be 700° C., 800° C., 900° C., 1000° C., etc.
[0098] The carbonization time may be 0.5-30 h, for example, 2 h-12 h, 2 h-24 h, 6 h-12 h, 6 h-24 h, etc.
[0099] The heating rate of the carbonization process can be 2-10°C / min.
[0100] Specifically, the carbonization can be carried out at a temperature of 700-1000° C. for 0.5-30 h; at a temperature of 800-900° C. for 2 h-24 h; or at a temperature of 800° C. for 6-12 h.
[0101] like Figure 4 As shown, the preparation method of the carbon fiber-based silicon-carbon composite material described in some embodiments of the present invention can be specifically:
[0102] Silicon powder and polydiallyldimethylammonium chloride (PDDA) are mixed, stirred and centrifuged in deionized water to obtain an intermediate product Si@PDDA in which silicon nanoparticles are coated with PDDA as a carbon source.
[0103] Then, the intermediate product Si@PDDA is mixed with a polymerizable monomer in a solution, and the first carbon source coated product Si@PDDA@RF is obtained by in-situ polymerization. The donor of the first carbon source is phenolic resin RF.
[0104] Subsequently, polyacrylonitrile PAN is dissolved in N,N-dimethylformamide DMF to obtain a polyacrylonitrile solution, and then the first carbon source coated product Si@PDDA@RF is added and mixed to obtain a spinning mixture, which is added to an electrospinning device to obtain spinning fibers CNF.
[0105] Finally, the spun fiber CNF is carbonized, and the PDDA is pyrolyzed to disappear, thereby constructing the gap Gap between the silicon nanoparticles and the carbon coating layer of the first carbon source, and finally obtaining a silicon-carbon composite material Si@Gap@RF@CNF with a multi-dimensional carbon fiber core-shell structure.
[0106] In the embodiment of the present invention, polyacrylonitrile PAN and phenolic resin are RF carbonized to form a carbon shell, PDDA is pyrolyzed to leave a large number of voids, and silicon nanoparticles are evenly distributed in the RF carbonized carbon shell, and are evenly wrapped and distributed inside the carbon fiber. Small-sized silicon nanoparticles are embedded in porous carbon nanofibers by electrospinning, and PAN and RF are used as carbon sources. A multi-layer coating strategy is used to construct a unique multi-dimensional hybrid nanostructure, and the silicon-carbon core-shell structure is wrapped in the carbon nanofiber skeleton. Using multiple carbon layers as a supporting structure, the structural stress of the material during the cycle can be effectively dispersed, and the close combination of silicon particles and the conductive matrix is enhanced to prevent the internal silicon from expanding too much and causing structural rupture, which is also conducive to electron transmission and material diffusion. Small-sized silicon nanoparticles are evenly wrapped inside the carbon layer constructed by phenolic resin RF, and the core-shell structure silicon and carbon are tightly wrapped in the carbon nanofiber by electrospinning, so that the material obtains an excellent conductive carbon network, and improves the rate performance and cycle stability of the material.
[0107] In yet another embodiment, a negative electrode sheet is provided, comprising the negative electrode material of the embodiment of the present invention or prepared by using the negative electrode material of the embodiment of the present invention.
[0108] In yet another embodiment, a battery is provided, wherein the negative electrode is made of the negative electrode material of the embodiment of the present invention.
[0109] The battery may be a button cell.
[0110] The first discharge capacity refers to the ratio of the actual amount of electricity released by the battery during the first discharge process to the theoretical amount of electricity released per unit mass of active material. The capacity retention rate is the ratio of the current discharge capacity to the first discharge capacity after multiple charge and discharge cycles, which reflects the cycle stability and long-term performance of the battery. The first discharge capacity of the battery in the embodiment of the present invention is greater than 1360mAh·g -1 After 200 cycles, the battery capacity is > 1070 mAh g -1 .
[0111] First Cycle Efficiency (FCE) refers to the ratio of the reversible capacity of a battery in the first charge and discharge cycle to its theoretical capacity, usually expressed as a percentage. It reflects the utilization rate of the active material in the first cycle of the battery, as well as the extent of the side reactions between the electrode material and the electrolyte. The level of the first efficiency directly affects the initial performance and energy density of the battery. The first efficiency of the battery of the embodiment of the present invention can be above 88%, or even above 90%.
[0112] The following will further illustrate the preparation method of the carbon-silicon composite negative electrode material, the negative electrode sheet and the battery of the present invention with specific examples.
[0113] Example 1
[0114] (1) 50 g of silicon powder and 2 L of PDDA were introduced into 30 L of deionized water and stirred evenly. The mixture was separated and the obtained product was washed and dried and recorded as Si@PDDA for later use.
[0115] (2) The product Si@PDDA of step (1) was added into a beaker, and 0.01 L ammonia water (mass fraction 20%), 150 g resorcinol and 10 L deionized water were added at the same time. After stirring with ultrasound (power 40 kHz, time 10 min), 0.015 L formaldehyde solution (mass fraction 37%) was gradually added dropwise, stirred evenly, separated, and the obtained product was washed and dried and recorded as Si@PDDA@RF for standby use.
[0116] (3) 450 g of PAN was dissolved in 5 L of DMF solution (80 g / L), and the product of step (2) was added and mixed evenly to obtain a spinning mixture, which was passed through an electrospinning device with specific process parameters including: using a 5 mL syringe, setting the distance between the needle tip and the aluminum foil to 15 cm, the device voltage to 155 kV, and the feed rate to 1 mL / h to obtain spinning fibers.
[0117] (4) The spun fiber of step (3) is placed in a tubular furnace for carbonization treatment at a carbonization temperature of 800° C., a carbonization time of 6 h, and a heating rate of 3° C. / min to obtain a final product, a carbon-silicon composite material with a multidimensional carbon fiber core-shell structure.
[0118] After testing, the SEM image of the carbon-silicon composite material of this embodiment is as follows: Figure 1 As shown in (1 μm), it can be seen from the figure that the silicon-carbon composite material prepared in this embodiment presents a multi-dimensional hollow fiber strip structure; Figure 2 (0.5 μm) is the TEM image of the silicon-carbon composite material prepared in this example. From the analysis of the image, it can be seen that the Si@PDDA@RF particles are evenly distributed in the carbon fiber skeleton structure.
[0119] Example 2
[0120] (1) 100 g of silicon powder and 2 L of PDDA were introduced into 35 L of deionized water and stirred evenly. The intermediate product was separated, washed and dried, and recorded as Si@PDDA for later use.
[0121] (2) The product of step (1) was added to a beaker, and 0.02 L of ammonia water (mass fraction 20%), 180 g of resorcinol and 12 L of deionized water were added at the same time, and the mixture was stirred after ultrasonic treatment (power 40 kHz, time 10 min), and then 0.02 L of formaldehyde solution (mass fraction 37%) was gradually added dropwise, and the mixture was stirred evenly. The product was separated and washed and dried;
[0122] (3) 650 g of PAN was dissolved in 6 L of DMF solution (80 g / L), and the product of step 2 was added at the same time. After mixing evenly, a spinning mixture was obtained, and spinning fibers were obtained by electrospinning equipment. The process parameters of the electrospinning equipment included: using a 5 mL syringe, the distance between the needle tip and the aluminum foil was set to 15 cm, the equipment voltage was 155 kV, and the feed rate was 1 mL / h.
[0123] (4) The spun fiber in step 3 is placed in a tubular furnace for carbonization treatment at a carbonization temperature of 800° C., a carbonization time of 6 h, and a heating rate of 3° C. / min.
[0124] Example 3
[0125] (1) 20 g of silicon powder and 1 L of PDDA were introduced into 10 L of deionized water and stirred evenly, and the intermediate product was separated, washed and dried;
[0126] (2) Add the product of step 1 into a beaker, add 0.01L ammonia water (mass fraction 20%), 150g resorcinol and 10L deionized water, stir after ultrasonication (power 40kHz, time 10min), then gradually drop 0.01L formaldehyde solution (mass fraction 37%), stir evenly, separate the product and wash and dry;
[0127] (3) 300 g of PAN was dissolved in 4 L of DMF solution (80 g / L), and the product of step 2 was added to the DMF solution to obtain a spinning mixture. After mixing evenly, the mixture was passed through an electrospinning device to obtain spinning fibers. The process parameters of the electrospinning device included: a 5 mL syringe, a distance between the needle tip and the aluminum foil was set to 15 cm, a device voltage of 155 kV, and a feed rate of 1 mL / h.
[0128] (4) The spun mixed fiber of step 3 is placed in a tubular furnace for carbonization treatment at a carbonization temperature of 800° C., a carbonization time of 6 h, and a heating rate of 3° C. / min.
[0129] Example 4
[0130] (1) 50 g of silicon powder and 2 L of PDDA were introduced into 30 L of deionized water and stirred evenly, and the intermediate product was separated, washed and dried;
[0131] (2) Add the product of step 1 into a beaker, add 2.4 L of deionized water and disperse by ultrasonic (power 40 kHz, time 10 min), add 290 g of tris (hydroxyaminomethane) until it is completely dissolved, then add 60 g of PDA, stir well, centrifuge to separate the product, and wash and dry;
[0132] (3) 450 g of PAN was dissolved in 5 L of DMF solution (80 g / L), and the product of step 2 was added at the same time. After mixing evenly, a spinning mixture was obtained, and spun fibers were obtained by electrospinning equipment. The process parameters of the electrospinning equipment included: using a 5 mL syringe, the distance between the needle tip and the aluminum foil was set to 15 cm, the equipment voltage was 155 kV, and the feed rate was 1 mL / h.
[0133] (4) The spun fiber in step 3 is placed in a tubular furnace for carbonization treatment at a carbonization temperature of 800° C., a carbonization time of 6 h, and a heating rate of 3° C. / min.
[0134] Comparative Example 1
[0135] Compared with Example 1, the difference is that the carbonization temperature in step (4) is different. The carbonization temperature is 600°C.
[0136] Comparative Example 2
[0137] Compared with Example 1, the difference is that the carbonization temperature in step (4) is different. The carbonization temperature is 1100°C.
[0138] Comparative Example 3
[0139] Compared with Example 1, the difference is that PDDA is not used as a sacrificial template to construct the gap
[0140] (1) 50 g of silicon powder was added to a beaker, and 0.01 L of ammonia water (mass fraction 20%), 150 g of resorcinol and 10 L of deionized water were added at the same time. After ultrasonication (power 40 kHz, time 10 min), the mixture was stirred. Then, 0.015 L of formaldehyde solution (mass fraction 37%) was gradually added dropwise, and the mixture was stirred evenly. The product was separated and washed and dried.
[0141] (2) 450 g of PAN was dissolved in 5 L of DMF solution (80 g / L), and the product of step (1) was added at the same time. After mixing evenly, a spinning mixture was obtained, and the spinning fiber was obtained by an electrospinning device. The process parameters of the electrospinning device included: a 5 mL syringe, a distance between the needle tip and the aluminum foil was set to 15 cm, an equipment voltage of 155 kV, and a feed rate of 1 mL / h.
[0142] (3) The spun fiber of step (2) is placed in a tubular furnace for carbonization treatment at a carbonization temperature of 800° C., a carbonization time of 6 h, and a heating rate of 3° C. / min.
[0143] Comparative Example 4
[0144] (1) 50 g of silicon powder and 2 L of PDDA were introduced into 30 L of deionized water and stirred evenly, and the intermediate product was separated, washed and dried.
[0145] (2) 450 g of PAN was dissolved in 5 L of DMF solution (80 g / L), and the product of step 1 was added at the same time. After mixing evenly, a spinning mixture was obtained, and spinning fibers were obtained by electrospinning equipment. The process parameters of the electrospinning equipment included: using a 5 mL syringe, the distance between the needle tip and the aluminum foil was set to 15 cm, the equipment voltage was 155 kV, and the feed rate was 1 mL / h.
[0146] (3) The spun fiber in step 2 is placed in a tubular furnace for carbonization treatment at a carbonization temperature of 800° C., a carbonization time of 6 h, and a heating rate of 3° C. / min.
[0147] The structural parameter test data of the carbon-silicon composite materials of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.
[0148] Fiber length (fiber skeleton): Take a SEM photo of the material and measure according to the scale in the figure.
[0149] Silicon content: measured by thermogravimetry (TG) at 1300°C in an oxygen atmosphere.
[0150] ID / IG: Raman test. Place the materials of Examples 1-4 and Comparative Examples 1-4 on the sample stage of the Raman spectrometer. Use a known reference sample (such as a silicon wafer) to calibrate the spectrometer. Set the test parameters, including a laser wavelength of 532nm and a test range of 100-4000cm -1 , the power is adjusted in time according to the actual test situation, and the scanning times are 3 times. .
[0151] Carbon layer thickness of Si@PDDA@RF: TEM image taken and measured according to the scale in the figure.
[0152] Particle size of Si@PDDA@RF: SEM image of the material, measured according to the scale in the figure.
[0153] Table 1 Structural parameter data of carbon-silicon composite materials
[0154]
[0155] Electrochemical performance test
[0156] The composite materials prepared in each embodiment and comparative example are prepared into negative electrode sheets, specifically:
[0157] The above samples were mixed with a conductive agent carbon black (Surper P) and a binder NMP (N-methylpyrrolidone) at a mass ratio of 96.5:1.5:2.0 to obtain a slurry, which was then coated on a copper foil to form a negative electrode sheet.
[0158] Assembling the battery
[0159] The prepared negative electrode plate and the lithium metal plate are assembled into a lithium-ion button cell, and LiPF6 is dissolved in an electrolyte of ethylene carbonate / diethyl carbonate / ethyl methyl carbonate = 2:3:1 at a concentration of 1 mol / L. After the button cell assembly is completed, the capacity, rate performance and cycle performance are tested using a Blue Electric charge and discharge tester.
[0160] Figure 5 The cycle performance test data of the button cell of the negative electrode sheet prepared by the material of Example 1 are shown. Test conditions 0.1, 0.2, 0.5, 1, 2, 5A g -1 The charge and discharge tests were carried out at current densities of 0.1, 0.2, 0.5, 1, 2, and 5 A g -1 The average discharge capacity is 1242 mAh g -1 , 1146mAh g -1 、1052mAhg -1 , 977mAh g -1 , 866mAh g -1 , 703mAh g -1 When the current density returns to 0.1A g -1 The average discharge capacity of Example 1 can still reach 1262 mAh g -1 The excellent rate performance reflects the excellent kinetic properties and electrochemical activity of the composite material.
[0161] Table 2 shows the electrochemical performance test results of the batteries of Examples 1-4 and Comparative Examples 1-4 (test conditions: 0.1C current density, 25°C constant temperature test cabinet).
[0162] Table 2 Electrochemical performance test results of button cells
[0163]
[0164] As shown in Table 2, the materials shown in Examples 1-4 are compared with Comparative Example 4. The 3D silicon-carbon core-shell structure is wrapped in a 1D carbon nanofiber skeleton, which can not only use carbon nanofibers as a supporting skeleton to enhance the overall mechanical strength of the material, but also further improve the electrochemical performance of the material through the synergistic effect between carbon nanofibers and carbon shells. Compared with Comparative Examples 1-3, PDDA is used as a sacrificial template to construct a gap, and the core-shell structure particles formed by RF resin coating single silicon particles (there is a gap between RF and silicon particles, formed by thermal decomposition of PDDA) are redistributed inside the PAN fiber, and the fiber structure crosses / intersperses to form a tight and stable network structure, which is conducive to the improvement of electrochemical performance.
[0165] Due to the formation of solid electrolyte interface (SE I) film on the surface of the electrode material or other side reactions, the increase in the first discharge specific capacity may be accompanied by an increase in irreversible capacity loss during the first charge process. These irreversible capacity losses may persist in subsequent cycles, thereby affecting the long-term capacity retention rate of the battery. The materials shown in Examples 1-4 have a unique multi-dimensional carbon fiber core-shell structure, which effectively disperses the mechanical stress caused by the deformation of silicon particles. At the same time, silicon nanoparticles are uniformly coated inside the carbon nanofibers, which improves the conductivity, rate performance and cycle stability of the composite material. The materials shown in Examples 1-4 have excellent electrochemical properties for the button cells of the negative electrode sheets prepared, not only showing excellent first discharge specific capacity, but also showing excellent first efficiency and capacity retention. It still has a high capacity after 200 cycles.
[0166] In the description of this specification, reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention.
[0167] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
[0168] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A carbon fiber-based carbon-silicon composite material, characterized in that: The carbon-silicon composite material is a multidimensional carbon fiber core-shell structure, including a first core-shell structure and a second core-shell structure, wherein the first core-shell structure is a core-gap-shell structure, with silicon nanoparticles as the core and a carbon coating layer of the first carbon source as the shell; The second core-shell structure is distributed in the carbon fibers formed by the second carbon source with the first core-shell structure as the core.
2. The carbon fiber-based carbon-silicon composite material according to claim 1, characterized in that: One or more of the following conditions are met: a1) the donor of the first carbon source comprises resin or polydopamine; a2) the donor of the second carbon source comprises a spinnable polymer; a3) the gap uses polydiallyldimethylammonium chloride as a sacrificial template; a4) the thickness of the carbon coating layer of the first core-shell structure is 30-50 nm; a5) the particle size of the first core-shell structure is 100-300 nm; a6) the particle size of the silicon nanoparticles is 5-15 nm; a7) the length of the carbon fiber is 10-80 μm; a8) the carbon fiber is a hollow carbon fiber; a9) The silicon content of the carbon fiber-based silicon-carbon composite material is 30-45%; a10) The ID / IG value of the carbon fiber-based silicon-carbon composite material is 0.70-0.
90.
3. The carbon fiber-based carbon-silicon composite material according to claim 2, characterized in that: One or more of the following conditions are met: b1) the resin comprises phenolic resin or its derivatives; b2) the spinnable polymer comprises one or more of polyacrylonitrile, polyethylene oxide, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polystyrene and polyamide; b3) The ID / IG value of the silicon-carbon composite material is 0.75-0.
85.
4. A method for preparing a carbon fiber-based silicon-carbon composite material according to claim 1, characterized in that: The following steps are involved: S1: mixing silicon powder and surfactant in a solvent to obtain an intermediate product A; S2: taking the intermediate product A and mixing it with the polymerization monomer solution, and obtaining the first carbon source coated product B through in-situ polymerization; S3: adding the first carbon source coated product B to a spinnable polymer solution to prepare a spinning mixture and performing electrospinning to obtain spinning fibers; S4: The spun fibers in step S3 are carbonized to obtain the carbon fiber-based silicon-carbon composite material.
5. The preparation method according to claim 4, characterized in that: The step S1 satisfies one or more of the following conditions: c1) surfactants include polydiallyldimethylammonium chloride; c2) the solvent comprises deionized water; c3) The mass volume ratio of silicon powder to surfactant is 20-50g:1L; c4) The volume ratio of surfactant to solvent is 1-5:10-20.
6. The preparation method according to claim 4, characterized in that: The step S2 satisfies one or more of the following conditions: d1) the polymerizable monomers include a combination of at least one phenolic compound and at least one aldehyde compound, trioxane or glucose, or dopamine hydrochloride; The phenolic compound includes a polyphenol compound, and may further include at least one of resorcinol, alkylresorcinol, catechol, hydroquinone, pyrogallol or tannic acid; The aldehyde compound includes at least one of formaldehyde, rose formaldehyde, acetaldehyde, propionaldehyde, furfural, benzaldehyde, and butyraldehyde; d2) the mass ratio of the polymerized monomer to the silicon powder is 1-10:1; d3) the thickness of the coating layer of the first carbon source coated product B is 30-50 nm; d4) the particle size of the first carbon source coated product B is 120-250 nm; d5) the solution comprises an alkaline solution; d6) When the polymerization monomer is a combination of at least one phenolic compound and at least one aldehyde compound, trioxane or glucose, the molar ratio of the phenolic compound to the aldehyde compound is 5-9:
1.
7. The preparation method according to claim 4, characterized in that: The step S3 satisfies one or more of the following conditions: e1) the spinnable polymer comprises one or more of polyacrylonitrile, polyethylene oxide, polyvinyl alcohol, polyvinyl pyrrolidone, polyvinylidene fluoride, polystyrene and polyamide; e2) the concentration of the spinnable polymer solution is 30-350 g / L; e3) the solvent of the spinnable polymer solution comprises at least one of N,N-dimethylformamide DMF, dimethylacetamide DMAc, methanol or acetone; e4) the mass ratio of the spinnable polymer to the silicon powder is 5-20:1; e5) The electrospinning process parameters include: voltage 140-160 kV, feed rate 0.5-2 mL / h, and collection distance 12-20 cm.
8. The preparation method according to claim 4, characterized in that: The step S4 satisfies one or more of the following conditions: f1) the carbonization temperature is 700-1000°C; f2) the carbonization time is 0.5-30h; f3) The heating rate of the carbonization process is 2-10°C / min.
9. A negative electrode sheet, characterized in that: It comprises the carbon fiber-based carbon-silicon composite material according to any one of claims 1 to 3 or the carbon-silicon composite material prepared by the preparation method according to any one of claims 4 to 8.
10. A battery, characterized in that: A negative electrode comprising the negative electrode sheet according to claim 9 or a negative electrode made of the carbon-silicon composite material according to any one of claims 1 to 3 or the carbon-silicon composite material prepared by the preparation method according to any one of claims 4 to 8.
11. The battery according to claim 10, characterized in that: When the battery is a button cell, one or more of the following conditions are met: First discharge specific capacity>1360mAh·g -1 ; After 200 cycles, the specific capacity is > 1070 mAh g -1 ; The first efficiency is >87%.